Psychological Formation of The Student in The Process of Distance Learning - Yusupova Zamira Zaripovna (Zien Journals, 2022)
Currently, in the educational systems of many countries of the world there is a tendency to change the paradigm of education, which is caused by global changes in the sphere of world politics and economics in the context of the transition to the information society. At the same time, the task of humanizing education, creating conditions for creative active cognitive activity of students comes to the fore. The following article is devoted to the psychological formation of students in distance learning environment.
Keywords: distance learning; Internet technologies; psychological and pedagogical features of ICT; self-actualization